Synthesis, Spectral Characterization and Antibacterial Study of Schiff Base Metal Complexes Derived from 4-Bromo-N-[(E)-(5-chloro-2-hydroxyphenyl)methylidene]benzenesulfonamide - Khan, Farmanullah; Syed, Fatima; Iqbal, Arshiya; Khan, Zia-Ul-Haq; Ullah, Hamid; Khan, Shafiullah (Asian Journal of Chemistry, 2016)
A new sulfonamide Schiff based 4-bromo-N-[(E)-(5-chloro-2-hydroxyphenyl)methylidene]benzenesulfonamide prepared by refluxing 5-chloro-2-hydroxybenzaldehyde and 4-bromobenzenesulfonamide. The Schiff base was used as a complexing agent for the Cu, Co, Ni and Zn complexes. All the metal complexes were characterized by micro-analytical data, 1H NMR, FT-IR and electronic spectra. The spectral data suggest coordination of Schiff base ligand with metal through nitrogen and oxygen atom and proves the bidentate nature of ligand. The biological screening effect of Schiff base and their metal complexes were studied against Gram-positive and Gram-negative bacteria by disc-diffusion technique. The biological activity shows that complex exhibit higher antibacterial activity than that of Schiff base against tested bacteria.